Historiographical Studies of Ivan Tkachenko’s Teaching Activity (the Second Half of XX – Beginning of XXI Century) - Nadiya Kalinichenko (Pedagogical Discourse, 2013)
This article analyzes the historiographical sources which reveal important aspects of educator and innovator Ivan Tkachenko Gurievich’s heritage on managerial problems, student youth work training, the construction of model schools for the formation of a creative personality. The second half of the twentieth century is characterized by educational activities humanistic orientation, including well-known in Ukraine and abroad educators and innovators Vasil Sukhomlynsky and his colleague and associate Ivan Tkachenko, as well as based on the idea of ​​pedagogy of cooperation, appreciation of the individual, developing models of schools as areas of creativity, Joy Schools. The historiographical analysis of the educational activities of Ivan Tkachenko (second half of XX – beginning of XXI century.)is based on A.Ivanko’s, O.Filonenko’s dissertation research, N.Kalinichenko’s, H.Levchenko’s, V.Madzihon’s, A.Postelnyak’s, B.Hyzhnyak’s numerous scientific and methodological works. Promising directions for future research of the teacher and innovator Ivan Tkachenko’s heritage are designated.